Quantitative optical coherence tomography angiography of the peripapillary circulation in glaucoma - Simonett, Joseph M.; Huang, David; Jia, Yali (Annals of Eye Science, 2017)
The cause of glaucoma, a disease defined by degeneration of retinal ganglion cells associated with cupping of the optic nerve head (ONH) and progressive vision loss, continues to be debated despite numerous advances in ophthalmic imaging and diagnostics. Although elevated intraocular pressure is often implicated, many studies, using a variety of imaging techniques including plain fundus photography, fluorescein angiography, laser Doppler flowmetry, and color Doppler ultrasound (1-4), have suggested that insufficiencies of ONH circulation may play a role in glaucoma pathogenesis. While all of these imaging modalities have been informative, each has a set of limitations, including low spatial resolution, invasiveness, restriction to superficial vessels, lack of repeatability, and modality specific artifacts. Optical coherence tomography angiography (OCTA), an imaging technology that can produce high resolution, three-dimensional images of fundus microcirculation, is well suited to overcome many of these limitations (5).